The biology of sexual development of Plasmodium: the design and implementation of transmission-blocking strategies - Sinden, Robert E (BioMed Central, 2012)
A meeting to discuss the latest developments in the biology of sexual development of Plasmodium and transmission-control was held April 5-6, 2011, in Bethesda, MD. The meeting was sponsored by the Bill & Melinda Gates Foundation and the National Institutes of Health, National Institute of Allergy and Infectious Diseases (NIH/NIAID) in response to the challenge issued at the Malaria Forum in October 2007 that the malaria community should re-engage with the objective of global eradication. The consequent rebalancing of research priorities has brought to the forefront of the research agenda the essential need to reduce parasite transmission. A key component of any transmission reduction strategy must be methods to attack the parasite as it passes from man to the mosquito (and vice versa). Such methods must be rationally based on a secure understanding of transmission from the molecular-, cellular-, population- to the evolutionary-levels. The meeting represented a first attempt to draw together scientists with expertise in these multiple layers of understanding to discuss the scientific foundations and resources that will be required to provide secure progress toward the design and successful implementation of effective interventions.